Modelagem de uma planta didática multivariável e não linear - Thomas, Wallas Gusmão (2010)
The objective of this dissertation is to show the development of one nonlinear pilot plant model and multivariable using the step response. The pilot plant belongs to the course of industrial process control of IFES - SERRA (ES). From the physical equations of the process, are developed relationships of controlled variables in steady state at any point of operation. Using the step response, are mapped onto the time constants of the process according to the changes of the manipulated variables. The delay model is found using the least squares and step response. Finally we developed a simulator to compare the time response of the real plant with the proposed model.